ISSUES OF USING INFORMATION TECHNOLOGIES IN THE SECURITIES MARKET OF UZBEKISTAN - Evgeny Shek (Western European Studies, 2023)
In today's stock markets, information technology plays a key role in ensuring efficiency, speeding up processes and reducing transaction costs, increasing security and protecting data. This article explores the role and significance of IT technologies in the stock market of Uzbekistan.
Keywords: Technologies; stock market; availability of information; traders